Effects of task type and language proficiency on dialogic performance and task engagement. (April 2022) - Garcia-Ponce, Edgar Emmanuell; Tavakoli, Parvaneh
Abstract: This study examined the effects of task type and English proficiency on L2 learners' task performance and engagement. By collecting data from 15 learner dyads at three levels of proficiency (elementary, intermediate and advanced) performing three dialogic tasks (personal information, narrative and decision-making tasks), we examined their performance in terms of complexity, accuracy, lexis and fluency (CALF), and degree of task engagement in three dimensions of cognitive, social and behavioural engagement. The results suggested that task type had an impact on all aspects of linguistic performance as well as social and behavioural engagement. While the personal information task elicited the most fluent and accurate language, it was the least engaging task in terms of social engagement. The narrative task elicited the most syntactically complex language, but it was the lowest in terms of behavioural engagement. Language proficiency influenced accuracy and fluency of performance as well as cognitive engagement with the task. The results showed that advanced learners were the most fluent, accurate and cognitively engaged group of learners across the tasks. In general, the results suggest that task type not only encourages specific dimensions of performance in CALF measures, but it could also affect learners' cognitive, social and behavioural engagement.